2002
DOI: 10.1111/1467-8381.t01-1-00154
|View full text |Cite
|
Sign up to set email alerts
|

Household Choice of Drinking–Water Source in the Philippines

Abstract: The present paper analyzes household choice of drinking-water source for 769 rural households in metropolitan Cebu, Philippines. The study aims to analyze the effects of input prices, tastes and household size on the choice probabilities. For the empirical analysis, a discrete-choice approach is employed, consistent with utility maximization. The findings indicate that the time cost is an important determinant of household choice of drinking-water source and, surprisingly, that taste, proxied by income, has am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…Households receiving a higher income, households with a more educated head, and larger households are more likely to have a private connection. These results confirm previous evidence that households with higher income and better education are usually more willing to get improved water services (Madanat and Humplick 1993;Hindman Persson 2002;Larson et al 2006;Nauges and Strand 2007;Basani et al 2008). Finally, the dummy variable describing concern about reliability of water from private well has the expected positive sign and is significant: the more concerned the household is about reliability of water from the private well, the higher the probability that she gets a private connection to the piped system.…”
Section: Determinants Of the Connection Statussupporting
confidence: 85%
“…Households receiving a higher income, households with a more educated head, and larger households are more likely to have a private connection. These results confirm previous evidence that households with higher income and better education are usually more willing to get improved water services (Madanat and Humplick 1993;Hindman Persson 2002;Larson et al 2006;Nauges and Strand 2007;Basani et al 2008). Finally, the dummy variable describing concern about reliability of water from private well has the expected positive sign and is significant: the more concerned the household is about reliability of water from the private well, the higher the probability that she gets a private connection to the piped system.…”
Section: Determinants Of the Connection Statussupporting
confidence: 85%
“…Money as a resource is used in purchasing water so once the household has enough to buy, the more it will be able to satisfy its daily requirement of water. This finding is in line with the works of Larson et.al (2006) and Hindman Persson (2002) which found a positive relationship between income and the choice of household water source. Consistency in the influence of per capita income on choice of water sources and deficiency in water demand of households provides enough justification for policy makers to understand the inequality among households in their ability to meet water demand and the consequent implication for their welfare in general and health in particular.…”
Section: Description Of Variablessupporting
confidence: 92%
“…Research in household choice of water sources have found a variety of explanatory variables ranging from piped water pressure level, presence of storage facility in the home, educational level and income (Madanat & Humplick, 1993;Larson, Minten, & Razafindralambo, 2006). Hindman Persson (2002) using multinomial logit model found annual labour income and walking time to the source of drinking water as determining choice of drinking water in the Philippines. Basani, Isham, and Reilly (2008), working on data from Cambodia, found that ethnicity, connection fee and expenditure on water was influential in determining the choice between five sources of water.…”
Section: Introductionmentioning
confidence: 99%
“…The survey results indicated that households cannot afford to pay for piped connections. Persson [35] analysed the choice of households in Philippines for drinking water sources. They argue that the demand for clean water for drinking purposes is derived demand, as it is an input to produce health.…”
Section: Review Of Existing Literaturementioning
confidence: 99%
“…Some studies also apply maximum likelihood estimation methods to analyse water demand using multinomial logistic and probit models [30,35] while others use either two stage least square methods [29], or systems of demand equations [4].…”
Section: Empirical Setupmentioning
confidence: 99%